SERANGAN DACUS CUCURBITAE ( DIPTERA: TRYPETIDAE) PADA BUAH MENTIMUN DAN PARE YANG DIBUNGKUS PADA SAAT PENTIL - I Gede Swibawa, F.X. Susilo, Indra Murti, dan Esti Ristiyani . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
Dacus cucurbitae ( Diptera: Trypetidae) attacks  on cucumber and peria fruits wrapped at cherelle stage. The fruit flies were important pests of cucumber (Cucumis sativus L) and peria (Memordica charantia L.).  The flies attacked fruits by laying egg on the fruit surface and their developing immatures caused serious damages from the inside. The objective of this experiment was to determine the effect of the  fruit wrapping at cherelle stage  on fruit fly infestation on  cucumber or peria fruits.   The experiment was conducted in villages of Terbanggi Besar (Central Lampung) and Jati Agung  (South Lampung) during October—November 2001. A set of cherelle stage fruits, i.e. those just shed off their florescence, were wrapped using plastic bags while another set of adjacent fruits were left unwrapped. Fruits (treated or untreated) were taken soon after they fell off or at their normal harvest time, whichever came first, then were weighed and incubated in the laboratory to observe the fruit fly emergence.  The results showed that fruit wrapping significantly reduced the fruit fly infestation and suppressed the fruit fly population on cucumber or peria fruits. The wrapped fruits weighed more than unwrapped fruits